Village-level supply reliability of groundwater irrigation in rural China: Effects of climate variables and tubewell density - Li, Yanrong; Wang, Jinxia; Huang, Jikun; Adhikari, Bihm; You, Liangzhi (Emerald Publishing Limited, 2018)
Purpose The purpose of this paper is to examine the status of the supply reliability of groundwater irrigation, and discuss how it is affected by climate change and tubewell density in rural China.